-3(-5v-4v-4y+3)=

Simple and best practice solution for -3(-5v-4v-4y+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-5v-4v-4y+3)= equation:


Simplifying
-3(-5v + -4v + -4y + 3) = 0

Reorder the terms:
-3(3 + -5v + -4v + -4y) = 0

Combine like terms: -5v + -4v = -9v
-3(3 + -9v + -4y) = 0
(3 * -3 + -9v * -3 + -4y * -3) = 0
(-9 + 27v + 12y) = 0

Solving
-9 + 27v + 12y = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 27v + 9 + 12y = 0 + 9

Reorder the terms:
-9 + 9 + 27v + 12y = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 27v + 12y = 0 + 9
27v + 12y = 0 + 9

Combine like terms: 0 + 9 = 9
27v + 12y = 9

Add '-12y' to each side of the equation.
27v + 12y + -12y = 9 + -12y

Combine like terms: 12y + -12y = 0
27v + 0 = 9 + -12y
27v = 9 + -12y

Divide each side by '27'.
v = 0.3333333333 + -0.4444444444y

Simplifying
v = 0.3333333333 + -0.4444444444y

See similar equations:

| (4x^(2/7))(3x^(1/3)) | | 9*(z-3)=12z | | 5x-105=-4x+30 | | -3x-7+2x+5x-11x= | | 5x-x-7=-4x+2 | | (3x+1)+4i=-2+(3y-2)i | | 0.5x^2-3x+4=0 | | 10x+64+5x=65x-36 | | -3-2(6)= | | -2(x+6)+3x= | | 3x-10=5x+45 | | 6y=10x-4 | | 3x+2y=73 | | 5x-6+6x-8=x+4+x+10 | | x^2+8=-8x+1 | | 10x-7y=11 | | 600t^2+60t-3=0 | | 140=x^(1/2) | | 140=x^1/2 | | 6a-(4a+7)= | | 2(cos(2x))+2=0 | | 4y=-3x+2 | | 9(x+4)-6(x-2)=3(x+16) | | 7x=9-3(x-1) | | (x-3)2=(3x-5)2 | | (27.9-18.6)/3.1 | | 3.5=14 | | (x-3)-(5-3x)=2x(x+1) | | 6x-3+x-4=4x+5+3x | | 2x^2+(2-i)x+1=0 | | 25y^2-100x^2=0 | | v^2+2v+7=0 |

Equations solver categories